Applications of T1 and T2 relaxation time calculation in tissue differentiation and cancer diagnostics—a systematic literature review - Micek, Marta; Aebisher, David; Surówka, Justyna; Bartusik-Aebisher, Dorota; Madera, Michał (Frontiers in Oncology, 2022)
The purpose of this review was to summarize current applications of non-contrast-enhanced quantitative magnetic resonance imaging in tissue differentiation, considering healthy tissues as well as comparisons of malignant and benign samples. The analysis concentrates mainly on epithelium and epithelial breast tissue though, especially breast cancer. A systematic review has been performed based on recommendations provided currently by publishers and foundations. By creating a search strategy and clear inclusion and exclusion criteria an exhaustive overview of currently used techniques and of their potential in medical sciences was obtained. PubMed and Elsevier (Scopus & Science Direct) search was narrowed down to studies reporting T1 or T2 values of human tissues, resulting in 404 initial candidates, out of which roughly 20% were found relevant and fitting the review criteria. Nervous system, especially brain, and connective tissue such as cartilage were the most frequently analyzed, while breast remained one of the most uncommon subjects of studies. There was not much agreement between published T1 or T2 values and methodologies and experimental setups differed strongly. Few contemporary (after 2000) resources have been identified that were dedicated to studying relaxation times of tissues and their diagnostic applications. Most of the publications concentrate on recommended diagnostic standards, for example, for breast, acquisition of T1- or T2-weighted images with use of gadolinium-based contrast agents. Not enough data is available yet to decide how repeatable or reliable analysis of relaxation times is in diagnostics, so it remains mainly a research topic. So far quantitative MRI might be recommended as a diagnostic help providing general insight into nature of lesions (benign vs malignant), but generally additional means are necessary to differentiate between specific lesion types.